HUMAN DEVELOPMENT INDEX (HDI) IN THE QUR'AN FROM THE QURAISH SHIHAB'S PERSPECTIVE - Khairina Tambunan; Isnaini Harahap; Azhari Akmal Tarigan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
The Human Development Index (HDI) is composed of three dimensions: education, health, and living standards. Using Islamic thought, this human development can be realized. The term human, which can be interpreted as a trust-bearing caliph, is associated with negative predispositions in themselves, and humans are associated with the process of human creation, which refers to psychological and spiritual traits, in the Quran Surah 51 verse 56. The study's goal is to look into how the concept of human development is defined in QS. Tafsir Al Misbah 51: 56 The hermeneutic method was used, with the interpretation of Quraish Shihab through the interpretation of Al-Misbah. According to the findings, Shihab defines worship as